Analisis Dan Perancangan Ulang Proses Bisnis Smart Laundry Dengan Pendekatan Value Added Dan Antrian - M. Zaki Efendi; Anisa Fitriani; Aisyah Azzahra; Ufatili Jannah; Tintia Dea Zammiati; Muhamad Anggun Novembra (LKP KARYA PRIMA KURSUS, 2025)
Smart Laundry is a laundry service business located in Padang City, offering single-item and bulk laundry services. Based on observations and interviews, several issues were identified in the current business processes, such as manual data recording, long ironing queues due to limited equipment, and unscheduled procurement of operational materials. This study aims to analyze and redesign the business processes of Smart Laundry using the Business Process Reengineering (BPR) and Business Process Management (BPM) approaches. The methods applied include Value Added Analysis to classify value-added activities and queue analysis to assess service efficiency. The results show that the laundry intake process and monthly data recapitulation are the most critical areas requiring improvement. The redesigned process includes the implementation of a digital system for data recording and monthly recaps, as well as recommendations to add ironing equipment, washing machines, and human resources to accelerate the service flow. With these improvements, Smart Laundry is expected to enhance operational efficiency, reduce customer waiting times, and support sustainable business growth.